An Analysis of the Qur'an Values in Pancasila and Its Application of Mathematics Learning - Ahmad Zarnuji; Isnaini Nur Azizah; Muhammad Nur Amin; Eka Prasetyawati (CV. Creative Tugu Pena, 2022)
Pancasila was the basic ideology of the Indonesian nation. The values ​​contained in Pancasila underlie all aspects of the social life of the Indonesian people. But now the reality, trans-national Islamic ideologies appear among some Indonesian. Citizens of radical groups strongly oppose the formulation of Pancasila as the state ideology. Among these groups was Hizbut Tahrir Indonesia (HTI). HTI rejects (3rd precept) Indonesian unity as the constitutional principle of the Indonesian nation. Democracy was seen as inconsistent with Islamic principles. Even Pancasila was called a kufr ideology that must be rejected because it is contrary to the Qur'an. The purpose of this study is to determine the relevance of the values ​​of the Qur'an with the meanings contained in Pancasila and how to instill the values ​​of the Qur'an and Pancasila in learning mathematics. Pancasila as the ideology of the Indonesian nation does not conflict with the Qur'an. The values ​​of the Qur'an were contained in the elaboration of each precept. What was taught in Pancasila actually taught in the Qur'an. The values ​​of the Qur'an in Pancasila can actually be applied in learning mathematics. Hence, the integration between mathematics and the Qur'an can be realized. Keywords: The Values Qur’an, Mathematics Learning, Integrated Qur’an